Strategi Kepala Sekolah dalam Meningkatkan Prestasi Peserta Didik Melalui Bina Prestasi di SMA Negeri 1 Gresik - Choirotin Nisak; Ayu Wulandari; Budi Purwoko; Amrozi Khamidi; Mochamad Nursalim; Kaniati Amalia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the school principal's strategy in improving student achievement through an achievement development program. This research was carried out at SMA Negeri 1 Gresik, which is the favorite school in Gresik district. Hundreds of SMAN 1 Gresik students have won various competitions at district, provincial and national levels. Various kinds of achievements, both academic and non-academic, have been achieved every year. This research aims to explore more deeply the principal's strategy for improving student achievement through achievement development. This research uses a qualitative descriptive research methodology with a case research type. Data collection techniques include in-depth interviews, observation and documentation. After verification, restatement, or reduction of the data obtained, conclusions are presented. Conclusion,that the achievement development program implemented at SMAN 1 Gresik to improve student achievement through the principal's strategy in planning, organizing, implementing and supervising is very effective in preparing students to take part in various achievement events, both academic and non-academic, both at district, provincial and national levels. Keywords: Achievement Development, Principal's Strategy, Student Achievement